La douleur des autres : Eisenstein, Mavrikakis et Agnant - Evelyne Ledoux-Beaugrand (Atlantis)
Abstract This article analyses narratives set against the backdrop of collective trauma, such as Bernice Eisenstein’s I Was a Child of Holocaust Survivors (2006), Catherine Mavrikakis’ Le Ciel de Bay City (2008), and Marie-Célie Agnant’s The Book of Emma (2004). Building upon the definition of pain as the “physical life of a story” (Ahmed 2004), it offers a reflection on the relationships between the pain experienced by others, the body and a traumatic history. Ultimately, it comes down to considering a politics of feminist pain from the reading of these texts.